RESEARCH OF THE INFLUENCE OF LASER BEAM PARAMETERS ON THE NEOPRENE LASER ENGRAVEMENT AND LASER CUT - Silinieks, Matīss; Geršebeks, Kristiāns; Tutiņa, Amanda; Lazov, Lyubomir (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2021)
The report considers the possibility of using laser technology for neoprene engraving and cutting. This modern material is a type of synthetic rubber with great strain resistance, general durability and excellent temperature insulation properties. This study uses a CO2 laser system SUNTOP ST-CC 9060 with a wavelength of 10640 nm with a goal to achieve the best engraving and cutting quality of the material and Zwick / Roell machine for testing the samples. As a result of experimental studies, power density and processing speed parameters were optimized for high – quality engraving and cutting of the neoprene.